2017
DOI: 10.1101/238865
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual differences in motor noise and adaptation rate are optimally related

Abstract: Individual variations in motor adaptation rate were recently shown to correlate with movement variability or “motor noise” in a forcefield adaptation task. However, this finding could not be replicated in a meta-analysis of visuomotor adaptation experiments. Possibly, this inconsistency stems from noise being composed of distinct components which relate to adaptation rate in different ways. Indeed, previous modeling and electrophysiological studies have suggested that motor noise can be factored into planning … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
6
1
Order By: Relevance
“…This classical model was originally presented by Smith and colleagues (Smith et al, 2006) and posits a fast state , that learns and forgets quickly, and a slow state , that learns and forgets slowly, both adapting to the motor error. The model was fit using a Bayesian approach similar to that in van der Vliet et al (2018). Details of the model and the Bayesian fitting procedure used to estimate individual subject parameters are available in the supplementary materials.…”
Section: Methodsmentioning
confidence: 99%
“…This classical model was originally presented by Smith and colleagues (Smith et al, 2006) and posits a fast state , that learns and forgets quickly, and a slow state , that learns and forgets slowly, both adapting to the motor error. The model was fit using a Bayesian approach similar to that in van der Vliet et al (2018). Details of the model and the Bayesian fitting procedure used to estimate individual subject parameters are available in the supplementary materials.…”
Section: Methodsmentioning
confidence: 99%
“…1 and 2 illustrates a frequently observed characteristic of motor 190 adaptation: even at the late stages of training, performance continues to suffer from small, persistent 191 errors 3,4,8,15,31,[35][36][37] . Such persistent, steady-state errors are one of the fundamental predictions of 192 mathematical models of adaptation [11][12][13][14][15] in which performance is driven by an interaction between two 193 opposing forces, error-based learning, and trial-to-trial forgetting: 194…”
mentioning
confidence: 99%
“…Previous studies (Burge, Ernst et al 2008, van Beers 2009, Wei and Kording 2010, He, Liang et al 2016, van der Vliet, Frens et al 2018), provided evidence for the OI theory during visuomotor adaptation. They showed that the planning component of motor noise correlates positively with the adaptation rate while the measurement component correlates negatively, at least when the respective noise component experimentally is kept constant.…”
Section: Discussionmentioning
confidence: 81%
“…Existing tools for fitting adaptation models (Albert and Shadmehr 2018, van der Vliet, Frens et al 2018) can only estimate parameters from single experimental runs (changes over repeated trials in one task condition and one subject) despite the often hierarchical nature of the experiment (repeated trials interleaved with multiple conditions, multiple subjects). This is particularly problematic for two-state models due to their low identifiability (see results).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation